Analisis Pengendalian Internal atas Persediaan Barang Dagang pada Alfamidi Belawan - Sinambela, Putri Yulia Br; Sihombing, Halomoan; Samosir , Hendrik Elisa Sutejo (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Internal control is a very important part so that company goals can be achieved. Without internal control, company goals cannot be achieved effectively and efficiently. Inventory system generally means a system that manages the flow of inventory data related to activities in a company. The inventory system includes a system for recording goods sold, a system for recording goods purchased, a system for requesting and releasing merchandise from the warehouse, a physical counting system, a goods sales returns system. This research aims to determine the implementation of internal control and determine the inventory system at Alfamidi Belawan located at Jl. Belawan I Station, Medan, Belawan City, North Sumatra. The data collection method used was interviews, observation using qualitative descriptive.